THE USE OF SELF-ASSESSMENT TOWARDS STUDENTS’ READING BEHAVIOR (A CASE STUDY) - Lianisya Lianisya (Journal of English and Education, 2014)
This study intends to investigate the use of self-assessment towards students’ reading behavior using KWL (Know-Want-Learnt) framework and discover the students’ responses towards the use of self-assessment in students’ reading behavior of twelfth grader students of a private high school in Bandung. To meet the purposes, this study employs qualitative approach as the method to analyze the data gathered. Specifically this research meets the characteristics of a case study. The data are obtained from the interviews and the classroom observations. This study reveals that the use of self-assessment in classroom can motivate them to be actively involved in learning process, especially in reading activity. To some extent the teacher already followed the procedure of conducting self-assessment in the classroom as suggested by Westwood (2001) in terms of leading students to activate their prior knowledge. However, to some extent the teacher also violated the procedures in terms of the inconsistency in conducting self-assessment in the classroom. Furthermore, from the interview it is found that the students give positive responses to self-assessment since it can help them to maintain their reading behavior. Nevertheless, there are some negative response from students who stated that they did not know what exactly a function of self-assessment.